Setting up a parathyroid multidisciplinary team meeting: one year's experience, outcomes and learning points. Issue 3 (7th March 2018) - Hancox, S H; Sinnott, J D; Kirkland, P; Lipscomb, D; Owens, E; Howlett, D C
Abstract: Objective: A parathyroid multidisciplinary team meeting was set up at East Sussex Healthcare Trust, from November 2014 to November 2015, in order to improve and streamline services for patients with parathyroid pathology. Methods: Data were collected on all new referrals for hyperparathyroidism, and on the outcomes for each patient discussed at the meeting, including the number of operations and management outcomes. A survey was sent out to the members of the multidisciplinary team meeting to determine their perception of its effectiveness. Results: Seventy-nine new referrals were discussed throughout the year; 43 per cent were recommended for surgery, 41 per cent had a trial of conservative or medical management before re-discussion, and 16 per cent required further imaging. Ninety-two per cent of patients underwent an ultrasound, single-photon emission computed tomography/computed tomography or nuclear medicine (sestamibi) scan prior to the meeting. All ultrasound scans were performed by a consultant radiologist. Conclusion: The multidisciplinary team meeting has been successful, with perceived benefits for patients, improved imaging evaluation and efficiency of referral pathways, leading to more appropriate patient management.